Improving quality in design-focused services - Love, Terence (IADE/UNIDCOM, 2005)
This paper reports research investigating quality improvement in design services. It explores issues relating to the complex environment in which design services operate, and reviews quality improvement in this area in terms of the strong critiques of quality improvement methods from the Systems fields in which many quality-based methods originated. The paper concludes with suggestions for approaches to improving quality in design services that are systemically appropriate.